2019
DOI: 10.1007/s10162-018-00708-w
|View full text |Cite
|
Sign up to set email alerts
|

Neural ITD Sensitivity and Temporal Coding with Cochlear Implants in an Animal Model of Early-Onset Deafness

Abstract: Users of cochlear implant (CI) face challenges in everyday situations such as understanding conversations in noise, even with CIs in both ears. These challenges are related to difficulties with tasks that require fine temporal processing such as discrimination of pulse rates or interaural time differences (ITD), a major cue for sound localization. The degradation in temporal processing and ITD sensitivity are especially acute in those who lost hearing in early childhood. Here, we characterized temporal coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 69 publications
5
55
2
Order By: Relevance
“…The ITD sensitivity of IC neurons to bilateral CI stimulation degrades with increasing pulse rates, consistent with limitations in perceptual ITD sensitivity in human CI listeners (Chung et al, 2016b). This rate-dependent degradation of ITD sensitivity is more severe in early- deafened and unstimulated animals than in adult-deafened rabbits (Chung et al, 2019). We compared the dependence of ITD sensitivity on pulse rates to investigate whether bilateral CI stimulation during develop can restore ITD sensitivity over a wide range of pulse rates.…”
Section: Restoration Of Itd Sensitivity In Early-deaf Animals With Bimentioning
confidence: 64%
See 4 more Smart Citations
“…The ITD sensitivity of IC neurons to bilateral CI stimulation degrades with increasing pulse rates, consistent with limitations in perceptual ITD sensitivity in human CI listeners (Chung et al, 2016b). This rate-dependent degradation of ITD sensitivity is more severe in early- deafened and unstimulated animals than in adult-deafened rabbits (Chung et al, 2019). We compared the dependence of ITD sensitivity on pulse rates to investigate whether bilateral CI stimulation during develop can restore ITD sensitivity over a wide range of pulse rates.…”
Section: Restoration Of Itd Sensitivity In Early-deaf Animals With Bimentioning
confidence: 64%
“…The difference in relative fractions of excitatory/suppressive response might be driven by differences in spontaneous activity of the IC neurons. We have previously shown that there was no significant difference in spontaneous firing rates in AD, ED-US and normal hearing animals (Chung et al, 2019). Figure 7C compares the distribution of SR in three deafness groups and normal hearing rabbits.…”
Section: Chronic CI Stimulation Did Not Improve Temporal Coding In Eamentioning
confidence: 81%
See 3 more Smart Citations